The Study of Coastal Vulnerability in North Insana District, North Central Timor Regency, East Nusa Tenggara Province (Indonesia) - Ludgardis Ledheng; Blasius Atini; Emanuel Maria Yosef Hano’e (Jurnal Ilmu Lingkungan, 2025)
The reduction in mangrove areas, which has caused significant erosion along the north coast of North Central Timor Regency, has implied the need for in-depth studies. This research, aimed to determine the spatial distribution of coastal vulnerability and its influencing factors using the Coastal Vulnerability Index (CVI). The research found that 7.07 km (48.71%) of the coastline was classified as low vulnerability, while 6.66 km (51.28%) was categorized as moderate. Key factors influencing coastal vulnerability include geomorphology (87.18%), coastline changes (7.6%), beach slope (66.6%), and beach elevation (66.7%), based on observations across 39 cells. Meanwhile, tidal variables, wave height, and sea-level rise had minimal impact, with their associated vulnerability levels categorized as low. Future research should incorporate additional variables, such as socio-economic aspects and human activities to provide a more comprehensive assessment of coastal vulnerability. This would result in a more holistic assessment for decision-making for coastal area mitigation planning.